2015
DOI: 10.4014/jmb.1506.06025
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Toxin Genes and Enterotoxins in Bacillus thuringiensis Isolated from Microbial Insecticide Products

Abstract: Bacillus thuringiensis microbial insecticide products have been applied worldwide. Although a few cases of B. thuringiensis foodborne illness have been reported, little is known about the toxigenic properties of B. thuringiensis isolates. The aims of this study were to estimate the pathogenic potential of B. thuringiensis selected from microbial insecticide products, based on its possession of toxin genes and production of enterotoxins. Fifty-two B. thuringiensis strains selected from four kinds of microbial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The latter arises from an infection with vegetative cells, which produce enterotoxins, mainly the non-haemolytic enterotoxin (Nhe), haemolysin BL (Hbl) and cytotoxin K (CytK), in the human intestine [ 13 , 14 , 15 , 16 , 17 ]. Like B. cereus , B. thuringiensis exhibits the enterotoxin genes nhe, hbl and cytK [ 18 , 19 , 20 ]. Moreover, B. thuringiensis could be related to food-borne outbreaks [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The latter arises from an infection with vegetative cells, which produce enterotoxins, mainly the non-haemolytic enterotoxin (Nhe), haemolysin BL (Hbl) and cytotoxin K (CytK), in the human intestine [ 13 , 14 , 15 , 16 , 17 ]. Like B. cereus , B. thuringiensis exhibits the enterotoxin genes nhe, hbl and cytK [ 18 , 19 , 20 ]. Moreover, B. thuringiensis could be related to food-borne outbreaks [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…These two bacteria are highly similar in biochemical results (Böhm et al, 2015), and genetic properties (Osman et al, 2015). Cho et al (2015) also reported that the genetic and phenotypic properties between these bacteria are barely distinguishable. Furthermore, Pfrunder et al reported that B. cereus group species cannot be reliably identified using classical biotyping (Pfrunder et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The emetic syndrome caused by an intoxication is characterised by an acute attack of nausea and emesis occurring within 1-5 hours after consumption, caused by cereulide, a heat stable, ringstructured dodecadepsipeptide toxin [15,16] . The diarrheal syndrome characterised by abdominal pain and diarrhea, with an incubation period of 4-16 h and symptoms that last for 12-24 h, can be caused by the enterotoxincomplexes nonhaemolytic enterotoxin (NHE), haemolysin BL (HBL) and enterotoxin FM (EntFM) and the single protein cytotoxin K (CytK) [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%